Transversus abdominis and core stability - has the pendulum swung? - Allison, Garry; Morris, S. (BMJ Publishing Group, 2008)
In the past decade there has been a focus on isolated transversus abdominis activation and how it contributes to lumbo-pelvic stability. This rationale has not only influenced the management of chronic low back pain (LBP); it has also been included in exercises for many other pathologies of the lower and upper limb and also for prophylaxis in pain-free subjects.